Biocontrol potential of Bacillus velezensis SEC-024A against southern blight of industrial hemp - Wang, Tuhong; Li, Wenting; Wang, Fang; Li, Jiayang; Qin, Jingjing; Song, Zhiqiang; Xu, Jianping; Qiu, Huajiao; Cheng, Yi (Industrial crops and products, 2024)
Agroathelia rolfsii is the causative agent of southern blight of industrial hemp, which is a soil-borne infection resulting in grave economic losses in industrial hemp (Cannabis sativa L.). Chemical pesticides are currently the primary means of controlling this disease, but their use is harmful to human health as well as to the environment. Urgent action is needed to screen eco-friendly biocontrol agents against this pathogen. An endophytic bacterium SEC-024A was isolated from the leaf tissue of industrial hemp and exhibited a significant antagonistic effect on A. rolfsii, with a plate inhibition rate of 80.5 % and a pot control effect of 74.1 %. Through whole genome sequencing, SEC-024A was identified to be Bacillus velezensis. It contained multiple gene clusters involved in secondary metabolite biosynthesis and the genes that promote plant growth, colonization, and pathogen defense. Bacillus velezensis SEC-024A produces volatile organic compounds (VOCs) that serve as its primary fungistatic agents. Nine VOCs produced by SEC-024A were detected through gas chromatography-mass spectrometry. These VOCs were individually tested for their antifungal effects. Four volatiles, namely isobutyric acid, tiglic acid, trans-2-octenal, and 2-decanone, exhibited notable inhibitory effects on A. rolfsii with EC50 values of 0.012, 0.038, 0.009, and 0.046 μL/mL, respectively. Additionally, trans-2-octenal demonstrated broad-spectrum antifungal activity against various soil-borne pathogens. Together, this study suggests that B. velezensis SEC-024A holds promise as a novel microbial agent for improving plant growth and controlling diseases. •B. velezensis SEC-024A with antifungal activity against wide range of fungi was isolated from industrial hemp leaves.•The main antimicrobial agents of B. velezensis SEC-024A are isobutyric acid, trans-2-octenal, tiglic acid, and 2-decanone..•Trans-2-octenal showed broad-spectrum antifungal activity against various soil-borne pathogens.